Highlighting the mental health needs of Syrian refugees. Issue 2 (July 2015) - Almoshmosh, Nadim
<x xml:space="preserve">Abstract</x> This personal reflection discusses the author's personal involvement supporting the mental health needs of Syrian refugees. The mental health needs of this population includes a wide range of psychological problems that require further evaluation to fully understand. The scale of the problem is huge, affecting large numbers, some of whom were subjected to prolonged torture and witnessed daily bombardments. Many other factors add to the refugees' misery, including: their ordeal before reaching safety, uncertainty of the future, feelings of entrapment and humiliation. There are also the general effects of forced displacement, the stigma surrounding mental health issues, and lack of means and trained professionals. Host communities have been overwhelmed and unprepared to deal with such huge demands. While several aid agencies have been involved, there is a lack of coordination resulting in either missing out whole communites and duplication of efforts in others. Additionally, these challenging environments affect conducting studies with, often, highly frustrated populations and some results may be skewed as a result. This paper ends with suggestions of what can be done to improve approaches to providing some relief in this unprecedented and continuing crisis.